Redução fotocatalítica de nitrato e nitrito em água com característica potável - (:unkn) unknown (Universidade Estadual de Goiás, 2013)
The heterogeneous photocatalysis is a recent addition to the area of catalytic reduction of nitrate. Furthermore, photoreduction of nitrate and nitrite in aqueous solution appears as the most promising technology for the decontamination of waters by these species. The contamination of groundwater and surface water by nitrate and nitrite is increasingly common. The main sources of contamination are nitrogen fertilizers, breeding and septic tanks or rudimentary cesspools. High concentrations of nitrite and nitrate in water can cause serious risks such as eutrophication and health problems such as blue baby syndrome (methemoglobinemia), cancer, birth defects and mutation per share of nitrosamines. Because many sources of potable water characteristics are contaminated with these chemical species, we evaluated the removal of nitrate and nitrite in water by photocatalytic treatment developing and testing monometallic and bimetallic catalysts supported on oxides, conductive polymers and polymer composites in order to obtain maximum conversion and selectivity to nitrogen. The catalysts were synthesized by impregnation technique by evaporation of solvente, subsequent impregnation and photodeposition metal on the support. The photocatalytic tests were conducted in bench scale system, with the radiation source UV-C or UV-A, 64 mg of catalyst with 100 mL of solution with concentration is 100 mg NO3-.L-1 with H2 (g) or formic acid as a reducing agent. Ag/TiO2 catalysts showed good activity on average 450 mgNO3-.gcat-1.h-1 (with 75% conversion of NO3-), but with high selectivity to ammonia, about 13.6%. While the catalysts of Ag/Zeolite showed less activity, on average 45.5 mgNO3-.gcat-1.h-1 with high selectivity to N2(g) and low selectivity to ammonia, about 2%. Catalysts Ag/TiO2 and Ag/Zeolite were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), FTIR spectroscopy, atomic absorption spectrophotometry (AAS) and analysis of the specific surface area and volume pores. The catalysts supported on styrene-divinylbenzene or alumina showed no significant photocatalytic activity. The use of composites with polyaniline (PANI) did not increase the activity and selectivity of catalysts. The characterization by XRD led to the identification of the support and presence of silver confirmed in SEM and AAS; The method of preparation showed no difference in conversion to N2(g), but the brackets show differences in the activity and selectivity. The results are promising for further research with modifications of titania and zeolite.
Keywords: Fotoredução catalítica; Radiação UV; Prata; Titânia; Zeólita; Catalytic photoreductio; UV radiation; Silver; Titania; Zeolite; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL